Cutting Tool Technology - Smith, Graham T. (Springer, 2017)
It is a well acknowledged fact that virtually all of our modern-day components and assemblies – domestic, medical, industrial, automotive or aerospace, etc. – rely to some extent on machining operations in their manufacturing process. These wide-ranging manufactured components clearly show that there is a substantive machining requirement, which will continue to grow and thus be of prime importance for the foreseeable future. Cutting Tool Technology provides a comprehensive guide to the latest developments in the use of cutting tool technology. The book covers new machining and tooling topics such as high-speed and hard-part machining, near-dry and dry-machining strategies, multi-functional tooling, ‘diamond-like’ and ‘atomically-modified’ coatings, plus many others. Also covered are subjects important from a research perspective, such as micro-machining and artificial intelligence coupled to neural network tool condition monitoring. A practical handbook complete with troubleshooting tables for common problems, Cutting Tool Technology is an invaluable reference for researchers, manufacturers and users of cutting tools.